(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
Although “Exhumation” (lawful digging - out of already buried dead body), is rarity in our country; yet the CASES have attracted a lot of media attention, whenever it is done. Scientists from all streams of Forensic Sciences whether it be Anthropologist, Fingerprint Expert, Serologist, Forensic Odontologist or a Medicolegal Expert (doctor); are involved in the procedure along with other agencies like Police & Photographers.